Covid-19 and the catalyst to digital: implications on collection development strategy - Ram Nath, Nazimah (Institutional Knowledge at Singapore Management University, 2021)
The Covid 19 pandemic and subsequent lockdowns in various countries had a huge impact on academic institutions and how classes were being conducted and delivered. Online lessons became the new norm. Research needs and undergraduate learning activities also served up new challenges, when libraries shut due to nationwide lockdowns and travel restrictions. Academic libraries have found the need to shift their collection development practices and philosophies to ensure they can support teachers, students and researchers adequately in the short-term and long-term, regardless of geographical boundaries. One of the biggest change for the Singapore Management University library during the pandemic was the shift from supporting classroom-based instruction to online learning. To respond to the needs of the situation, the library took steps to shift our collection development practices to be more e-focused, shifting from collecting print books to e-books and exploring various e-book acquisition and subscription models. With faculty transitioning from face-toface instruction to online course delivery, we took the opportunity through active outreach to identify required teaching and resource materials where an online equivalent would be required. In addition, we also embarked on a Print-to-Electronic conversion exercise, – purchasing electronic versions of course reserve titles and subscribing to electronic textbooks via the Vitalsource platform, so students can access and read their core textbooks online, from anywhere. We also used this time to promote the access and discovery of open education resources (OERs) to instructors, researchers and students and started with adding 700 Open Textbooks to our discovery platform and supported online course delivery by digitizing some content to enable seamless access. Digitization of resources for course readings fared highly in the requests received and there was a need to ensure that empathy with the needs of the students should still be carried out without any infringement of copyright laws and be within the fair dealing and educational exceptions allowed. In the absence of emergency copyright exceptions, the library embarked on other strategies, like writing in for permission to publishers and also implement a pay-per-use licensing option. The pandemic was a catalyst for academic teaching, learning and access to academic resources to go digital. The SMU Libraries story is one about pivoting, being responsive and exercising flexibility in managing collection development, access to resources and copyright activities in an innovative way. This presentation will focus on how the SMU Libraries at the Singapore Management University was affected by COVID-19 and the steps they took to adjust their collection development practices, ensuring online access to library resources while at the same time managing copyright compliance.